Implementationand Performance Analysis of Multi Carrier-Direct Sequence-Code Division Multiple Accesson DSK TMS320C6416T - Kuswidiastuti, Devy; Suwadi, Suwadi; Suryani, Titiek; Efendi, Yusuf (JAVA Journal of Electrical and Electronics Engineering, 2015)
Wireless Digital Communication System nowadays must have the ability to provide a high data rate and highly reliable QoS. The application of multi carrier system offers a privilege in the spectrum efficiency aspect, because of the possibility of overlapping an orthogonal subcarrier. In MC-DS-CDMA system, some user sutilizing the same broadband frequency at the same time. Each user is distinguished by applying a unique spreading code. The problem is, the code sometimes becomes correlated with each other, hence affecting multi-user interference. This problem depends on the orthogonalities of the spreading codes that is used for each user. In this paper, implementation of MC-DS-CDMA system is done using DSK TMS320C6416T platform that is controlled via matlab simu link. Performance analysis of MC-DS-CDMA system is discussed from the aspect of resulting bit error rate (BER) parameter. Simulation and measurement are conducted to measure the real performance of the MC-DS-CDMA system prototype by giving a variation of the Eb/No value. From the measurement results, it shows a similarity with the expected theoretical result. The best result is obtained when the system operate with Eb/N0≥12dB. And the system failed to for Eb/N0≤4dB.